2017
DOI: 10.3389/fpls.2017.00341
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Genes Encoding Key Enzymes Involved in Anthocyanin Metabolism of Kiwifruit during Storage Period

Abstract: ‘Hongyang’ is a red fleshed kiwifruit with high anthocyanin content. In this study, we mainly investigated effects of different temperatures (25 and 0°C) on anthocyanin biosynthesis in harvested kiwifruit, and characterized the genes encoding key enzymes involved in anthocyanin metabolism, as well as evaluated the mode of the action, by which low temperature regulates anthocyanin accumulation in ‘Hongyang’ kiwifruit during storage period. The results showed that low temperature could effectively enhance the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 31 publications
5
24
0
Order By: Relevance
“…On the other hand, all gene expression was depressed at 30 . Similar lower expression of anthocyanin biosynthesis-related genes at elevated temperatures was reported in roses (Dela et al, 2003), grape (Mori et al, 2005), chrysanthemum (Huh et al, 2008), lily (Lai et al, 2011), and kiwifruit (Li et al, 2017). Huh et al (2008) reported the depressed expression of DFR and ANS in petals of two chrysanthemum genotypes at high temperature.…”
Section: Exp3 Effect Of Temperature On Gene Expression Of Key Enzymessupporting
confidence: 55%
“…On the other hand, all gene expression was depressed at 30 . Similar lower expression of anthocyanin biosynthesis-related genes at elevated temperatures was reported in roses (Dela et al, 2003), grape (Mori et al, 2005), chrysanthemum (Huh et al, 2008), lily (Lai et al, 2011), and kiwifruit (Li et al, 2017). Huh et al (2008) reported the depressed expression of DFR and ANS in petals of two chrysanthemum genotypes at high temperature.…”
Section: Exp3 Effect Of Temperature On Gene Expression Of Key Enzymessupporting
confidence: 55%
“…Here we show AcMYB123 specifies a typical R2R3‐MYB domain protein containing an R3 repeat with a conserved motif (D/E)LX 2 (R‐K)X 3 LX 6 LX 3 R that may confer the interacting ability with its bHLH partner of kiwifruit (AcbHLH42) demonstrated by the BiFC and Co‐IP assays (Figure ). Interestingly, phylogenetic analysis (Figure S3) of the R2R3‐MYB domain of AcMYB123 and the related MYB family members from various plant species indicates that AcMYB123 is more closely related to Arabidopsis TT2/AtMYB123, specifically required for regulating proanthocyanidin biosynthesis (Nesi et al ., ; Baudry et al ., ), than to anthocyanin regulators in both monocots and dicots, such as Arabidopsis AtPAP1/PAP2 (Borevitz et al ., ), maize C1 (Paz‐Ares et al ., ) and to other kiwifruit anthocyanin‐related MYB proteins (Fraser et al ., ; Man et al ., ; Li et al ., ,b; Liu et al ., ). Consistently, AcMYB123 is highly homologous to TT2‐like R2R3‐MYBs from strawberry ( Fragaria ananassa ) (FaMYB9/FaMYB11) and peach ( Prunus persica ) (Peace) (Figure S3) in anthocyanin or proanthocyanidin production (Nesi et al ., ; Schaart et al ., ; Uematsu et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the released kiwifruit genomes (Huang et al ., ; Pilkington et al ., ), AcMYBF110 and AcMYB123 localize to chromosomes 1 and 24, respectively, and appear to be under the control of different cis ‐regulatory elements (Figure S12) as indicated by their distinct expression patterns throughout fruit development (Figure c,d). Moreover, AcMYB5‐1 and AcMYBA1‐1 (Li et al ., ) are expressed throughout fruit development with a pattern similar to AcMYB123 (Figures d and S13a,b) but their bHLH partners are unknown. Intriguingly, the expression of AcMYB5‐1 and AcMYBA1‐1 was largely unaffected, in contrast to that of AcMYBF110/AcMYB75/AcMYB1/AcMYB10 that showed enhanced transcription by ectopic expression of AcMYB123 and AcbHLH42 in fruit flesh of A. arguta cv.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, HY5 and HYH were found to be necessary regulators for LT-induced anthocyanin accumulation in Arabidopsis thaliana (Gu et al, 2015). The transcript abundance of MYBA1-1 and MYB5-1 was up-regulated by LT to induce specific anthocyanin biosynthesis genes such as ANS1, ANS2, DFG1, DFR2, and UFGT2 in Actinidia chinensis (Li et al, 2017). High ambient temperature induces degradation of the HY5 protein in a COP1-activity-dependent manner to repress anthocyanin biosynthesis in A. thaliana .…”
mentioning
confidence: 99%